Unlocking the secrets to regenerating cardiac tissue: an update. (24th August 2017) - Kislitsina, Olga N; Revishvili, Amiran S; Cox, James L
Abstract: The use of extracellular matrix has evolved into a promising therapeutic approach for the treatment of valve disease and heart failure. Both biomechanical and biochemical signals for tissue remodelling require the presence of the extracellular matrix to recognize the remodelling signals and transfer them to the host stem cells. The extracellular matrix is the key to delivering these signals to the immigrated stem cells, and it also serves as a 'stem cell scaffold' making the possibility of regenerating new cardiac tissue a reality.